Empowering feedback through communication channels to strengthen conceptual learning during modular distance learning - Pantoja, Nathalie Gaile R. (Animo Repository, 2022)
As the Department of Education shifted from the face-to-face classroom to different distance learning environments due to the Covid-19 pandemic, providing frequent and ongoing feedback is a challenge for students and teachers alike. The use of feedback to assess learning is a powerful tool for ensuring that learning goals are met. This action research primarily sought to investigate the power of feedback in attaining learning targets in Physical Science through different communication channels of selected senior high school students. As modular learning was implemented for the SY 2020-2021, learning packages containing the modules, worksheets, and self-monitoring tools were distributed. Students were asked to submit their worksheet answers weekly with their self-monitoring tools to determine their initial difficulties, queries, and what they worked well with. Students used Google Forms and Facebook Messaging to submit their answered worksheets. Text messaging was used in all communication channels to keep students up to date and urge them to check their worksheets for feedback. After the four-week implementation, an adapted exam was administered via Google Forms to assess students’ conceptual understanding. Purposively selected students and parents were interviewed to further validate the quantitative data gathered. The submitted self-monitoring tools were gathered and analyzed. It showed that almost all participants did not need any assistance with answering the worksheets. It was also found out that before asking for assistance from the teacher, the student tends to access learning resources and ask their peers. An independent samples t‐test failed to report a significant difference between the test score for students who preferred sending hard copies and through Facebook messaging (M=8.04, SD=3.067) compared to students who preferred sending through Google Forms (M=9.00, SD=3.052; t(-.904)=37 p=.372), and a small to a medium effect was found (d=-.29, 95%, CI [-3.101‐1.188]). The findings also showed that across the communication channels, the class only obtained and average score (M=8.44, SD=3.243). The corresponding cognitive domains of the test items also showed that Remembering items had the highest mean (M=28.25, SD=2.363). This implied that empowering feedback could help strengthen conceptual understanding at low critical thinking skill level. Interview results showed that students utilized the feedback with its purpose, academic and emotional responses. It enticed the effect on student willingness to engage in learning. As parents were also a part of accomplishing the forms, parental involvement made students felt academically monitored, assisted, and emotionally supported. Overall, this implied that evident involvement of the teacher, parents, and the students in feedbacking may not entirely be beneficial to students’ conceptual understanding, but to their overall experience in learning during the modular learning environment.